Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation Dilengkapi LKPD 'Quis Interaktif' untuk Meningkatkan Hasil Belajar Siswa - Madik, Jeni Rosalina K.; Makaborang, Yohana; Ndjoeroemana, Yohana (MASALIQ, 2025)
This study aims to improve the learning outcomes of eleventh-grade students at SMA Negeri 1 Haharu through the implementation of the Group Investigation (GI) cooperative learning model, supplemented with the “Quis Interaktif” Student Worksheet (LKPD). This research uses a Classroom Action Research (CAR) design with 35 students as the research subjects. The instruments used include a learning outcomes test, observations, and questionnaires. The results of the study show that the application of the GI model with the “Quis Interaktif” LKPD can improve student learning outcomes. This is evident from the increase in the average learning score from Cycle I to Cycle II. In addition, student activity during the learning process also increased, as indicated by more active participation in discussions and collaboration within groups. Based on these findings, it is recommended that the GI cooperative learning model with the “Quis Interaktif” LKPD be implemented in other classes to effectively enhance student learning outcomes.